A Review on Framework and Quality of Service Based Web Services Discovery - Algaet, Mustafa Almahdi; Muhamad Noh, Zul Azri; Shibghatullah, Abdul Samad; Ahmad Milad, Ali (eurojournals, 2013)
Selection of Web services (WSs) is one of the most important steps in the application of different types of WSs such as WS composition systems and the Universal Description, Discovery, and Integration (UDDI) registries. The more available these WSs on the Internet are, the wider the number of these services whose functions match the various service requests is. Selecting WSs with higher quality largely depends on the quality of service (QoS) since it plays a significant role in selecting such services. In achieving this selection of the best WSs, the potential WSs are ranked according to the user’s necessities on service quality. In many cases, the value of QoS ontology is realized by its support for nonfunctional features of WSs. This ontology is also capable of providing solutions to the interoperability of QoS description. Moreover, based on the QoS ontology, it becomes more possible to develop a framework of semantic WS discovery. The framework enhances the automatic discovery of WSs and can improve the users’ efficiency in finding the best web services. Thus, Web Services are software functionalities publish and accessible through the Internet. Different protocols and web mechanism have been defined to access these Services.